Inhalation of Origanum majorana L. essential oil while working reduces perceived stress and anxiety levels of nurses in a COVID-19 intensive care unit: a randomized controlled trial - Lee, Sang Wook; Shin, You Kyoung; Lee, Jeong-Min; Seol, Geun Hee (Frontiers in Psychiatry, 2023)
Background: Nurses caring for patients with coronavirus disease 2019 (COVID-19) experience higher psychosocial distress than other healthcare workers, and this can adversely affect the quality of patient care. There is evidence that inhalation of essential oil from marjoram (Origanum majorana L.) has calming effects, suggesting this intervention may help to reduce the stress and anxiety of nurses working in a COVID-19 intensive care unit (ICU). This study aimed to investigate the effect of inhalation of marjoram essential oil at work on the stress and anxiety levels of nurses in a COVID-19 ICU.Methods: Nurses (n = 57) working in a single COVID-19 ICU were randomly assigned to inhale 3% marjoram essential oil (marjoram group, n = 29) or almond oil (control group, n = 28) for 2 h while at work. Mean arterial pressure (MAP), heart rate, state anxiety score, score on a visual analogue scale for anxiety (VAS-anxiety) and stress (VAS-stress) were measured before and after the intervention.The two groups had similar baseline variables. MAP did not have within-group or betweengroup differences. Heart rate increased significantly in the marjoram group after the intervention (P = 0.031), but it remained within the normal range and the increase was not clinically meaningful. There was no significant between-group difference in the state-anxiety or VAS-anxiety score after the intervention, but the marjoram group had significantly lower state-anxiety (P = 0.001) and VASanxiety (P = 0.037) score at posttest versus pretest. The VAS-stress score was significantly lower in the marjoram group at posttest versus pretest (P = 0.026).Nurses caring for patients in a COVID-19 ICU experience significant stress, and strategies are needed to address this important issue. Inhalation of 3% marjoram essential oil while caring for patients in a COVID-19 ICU may be a simple and effective intervention that reduces perceived stress and anxiety in nurses. 2 This is a provisional file, not the final typeset article Clinical trial registration: [https://cris.nih.go.kr/], identifier [KCT0007543].